PENGARUH SUHU DAN WAKTU PENYIMPANAN SERUM TERHADAP KADAR C-REACTIVE PROTEIN PADA PASIEN TUBERKULOSIS - Desta, Sally; Khairinisa, Gina; Tantan, Acep; Gita Naully, Patricia (JURNAL KESEHATAN KARTIKA, 2024)
Background : Tuberculosis is a chronic infectious disease that can be spread through air exposed to Mycobacterium tuberculosis bacteria. This disease can generally attack the lung organ which will then cause inflammation. Inflammation is a mechanism process carried out by the body in defending itself against foreign objects that enter the body. C-Reactive Protein is an acute protein produced by the liver and can be found in normal serum with a small amount, but will increase when given a stimulus such as infection, burns, and postoperative. Objective : to test CRP levels and determine the effect of temperature and storage time on CRP levels in the serum of Tuberculosis patients. Method : using Pre-experimental design one group pretest postest design, then data analysis using dependent T test and Wilcoxon test. This study conducted qualitative and semi-quantitative CRP examination on serum stored at room temperature (20-25℃) and refrigerator temperature (2-8℃) for 24 and 48 hours. Results : The results obtained at refrigerator temperature showed that the p-value> 0.05 had no significant relationship with serum stored in 24 and 48 hours. At room temperature, the p-value <0.05 is known to have a significant relationship. Conclusion : In this study, there was no effect on sample storage temperature on CRP levels examined at 0, 24, and 48 hours in the serum of tuberculosis patients. There was an effect on the length of sample storage on CRP levels examined at 0, 24, and 48 hours in the serum of tuberculosis patients.